Research on the coupling and coordinated development of Guangxi’s tourism industry, new urbanization and environmental health system in the post-epidemic era - Meng, Qiuli; Pi, Hongwen; Nie, Yu; Ma, Jixian (Frontiers in Public Health, 2024)
As one of China's sunrise industries, tourism has always been the engine to promote the development of the national economy, and in 2018, the annual income of China's tourism industry exceeded 5 trillion yuan unprecedentedly. In recent years, the traditional extensive production mode has inevitably brought about problems such as environmental pollution and public health threats, while helping the development of new urbanization, thus triggering a series of challenges in the environmental health system. The tourism industry, new urbanization, and environmental health system three cooperate and promote each other, the coordinated development between them for economic growth, new urbanization development, environmental protection, and public health play a vital role, in the post-epidemic era is a special period of historical opportunities, the public's focus from the original sacrifice of environmental health in exchange for economic growth model began to green, low-carbon sustainable development mode, Guangxi Zhuang Autonomous Region as a tourism resource endowment rich region, It is of positive significance to explore the coupling degree and coordination between the tourism industry, new urbanization and environmental health system, and put forward targeted practical enlightenment, which is of positive significance for promoting the sustainable development of tourism industry.